Analisis tingkat kesesuaian materi fisika SMA/MA dengan tujuan kurikulum - Luthfika Putri Antari; Ahmad Fauzi; Rifai Hamdi; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2020)
There are several processes in education, one of which is the curriculum. The curriculum is a tool to achieve educational objectives Without an appropriate and appropriate curriculum it will be difficult to achieve the educational goals and objectives to be achieved. As a useful tool for achieving a goal, the curriculum should be able to adapt to changing times and advances in science and the sophistication of technological developments. In 2013 the Indonesian government published a new curriculum called the 2013 curriculum to create a generation ready to face the challenges of the future. The purpose of the 2013 Curriculum itself is to prepare Indonesian people to have the ability to live as individuals who are faithful, productive, creative, innovative and affective citizens and are able to contribute to the life of society, nation, state and world civilization.Among the keys to success that determine the successful implementation of the 2013 Curriculum are learning facilities and resources. Thus, textbooks are still a very important source of learning for studentsMaterials or learning materials are basically the "content" of the curriculum, namely in the form of subjects or fields of study with topics / subtopics and their details. The 2013 Curriculum has a National Education Standard which is the goal in achieving the 2013 Curriculum. According to the BNSP, the National Education Standards serve as the basis for planning, implementing and supervising education in order to realize quality national education. The National Education Standards which are used as guidelines in assessing the suitability of curriculum objectives in high school Physics teaching materials which include 6 components, including compliance with Graduate Competency Standards, Core Competencies, Basic Competencies, Scientific Approach, Authentic Assessment and Local Content for learning objectives in the curriculum can be achieved. The results of this research are the material conformity of SMA / MA Physics with the curriculum objectives in class X semester 1 is 86%, class XI semester 2 is 89%, class XI semester 1 is 90%, class XI semester 2 is 93%, class XII semester 1 is 93% and class XII semester 2 is 88% with the whole semester getting the "very suitable" category. It can be concluded that the level of suitability of the SMA / MA Physics material with the Curriculum Objectives is 90% included in the "very suitable" category. This means that the Physics material for SMA / MA in each semester is in accordance with the Curriculum Objectives.